Corporate social responsibility and trade credit during periods of monetary contraction - Daxin Dong; Peng Liu (Journal of Applied Economics, 2022)
This paper studies whether firms' corporate social responsibility (CSR) affects their access to trade credit in response to monetary contraction shocks. Based on US firm-level data from 1995Q1 to 2014Q1, we find that after monetary contraction shocks, firms with higher levels of CSR receive more trade credit than firms with lower levels of CSR. Moreover, the beneficial impact of CSR is stronger for firms in regions with higher social trust and in more competitive industries. The interpretation of the observed phenomena is that the high-CSR firms are regarded as more trustworthy.
Keywords: 330; Corporate social responsibility; monetary contraction; trade credit; trust